Family formation among youth in Europe : coping with socio-economic disadvantages - Emirhafizović, Mirza; Heiman, Tali; Medgyesi, Marton; Mota, Catarina Pinheiro; Tomanovic, Smiljka; Vella, Sue (Perspectives on human development, 2022)
"This book, which has been created in the framework of the EU-funded COST Action YOUNG-IN (CA17114), sheds a light on the structural disadvantages and opportunities in family formation among youth, offering an insight into the relevant contextual factors in eleven countries. Analyzing demographic trends and socioeconomic settings, including normative and institutional frameworks (that focus on family policies), the authors have identified and presented the peculiarities of the transition to parenthood, as well as common challenges that young people face in that process"--